Proton pump inhibitor and histamine‐2 receptor antagonist use and risk of liver cancer in two population‐based studies. Issue 1 (9th May 2018) - Tran, K. T.; McMenamin, Ú. C.; Hicks, B.; Murchie, P.; Thrift, A. P.; Coleman, H. G.; Iversen, L.; Johnston, B. T.; Lee, A. J.; Cardwell, C. R.
Summary: Background: Proton pump inhibitors (PPIs) and histamine‐2 receptor antagonists (H2RAs) are commonly used. PPIs have been shown to promote liver cancer in rats; however, only one study has examined the association in humans. Aims: To investigate PPIs and H2RAs and risk of primary liver cancer in two large independent study populations. Methods: We conducted a nested case‐control study within the Primary Care Clinical Informatics Unit (PCCIU) database in which up to five controls were matched to cases with primary liver cancer, recorded by General Practitioners. Odds ratios (ORs) and 95% confidence intervals (95% CIs) for associations with prescribed PPIs and H2RAs were calculated using conditional logistic regression. We also conducted a prospective cohort study within the UK Biobank using self‐reported medication use and cancer‐registry recorded primary liver cancer. Hazard ratios (HRs) and 95% CIs were calculated using Cox regression. Results: In the PCCIU case‐control analysis, 434 liver cancer cases were matched to 2103 controls. In the UK Biobank cohort, 182 of 475 768 participants developed liver cancer. In both, ever use of PPIs was associated with increased liver cancer risk (adjusted OR 1.80, 95% CI 1.34, 2.41 and adjusted HR 1.99, 95% CI 1.34, 2.94 respectively). There was little evidence of association with H2RA use (adjusted OR 1.21, 95% CI 0.84, 1.76 and adjusted HR 1.70, 95% CI 0.82, 3.53 respectively). Conclusions: We found some evidence that PPI use was associated with liver cancer. Whether this association is causal or reflects residual confounding or reverse causation requires additional research. Abstract : Linked Content This article is linked to Waldum paper. To view this article visithttps://doi.org/10.1111/apt.14841 .